FACTORS INFLUENCING THE JOB SATISFACTION OF WOMEN EMPLOYEES IN EDUCATIONAL INSTITUTIONS – A STUDY WITH REFERENCE TO CHENGALPET DISTRICT (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to examine the employees’ job satisfaction in Chengalpet district. Specifically, this research aims to assess the impact of independent variables such as employee recognition, job security, rewards and employee job satisfaction, leadership and accountability as dependent variable.This article mainly focuses on the factors influencing job satisfaction of employees in Educational Institutions in Chengalpet District.